Kinase partner protein interacts with the LePRK1 and LePRK2 receptor kinases and plays a role in polarized pollen tube growth - Kaothien, Pulla (2005)
The pollen-specific receptor kinases LePRK1 and LePRK2 have localization and expression profiles that strongly suggest they play roles in pollen germination and tube growth. To identify downstream components of LePRK signaling, we used their cytoplasmic domains (CDs) as baits in yeast two-hybrid screens of a tomato pollen cDNA library. A pollen-specific protein we named kinase partner protein (KPP) interacted with the CDs of both LePRK1 and LePRK2 in yeast and in an in vitro pull-down assay, and with LePRK2 in a co-immunoprecipitation assay. KPP is a peripheral membrane protein and is phosphorylated in pollen. Pollen tubes over-expressing KPP developed balloon-like tips with abnormal cytoplasmic streaming and F-actin arrangements and plants over-expressing KPP exhibited impaired transmission of the transgene through the male. KPP-like genes are found only in plants; the 14 family members in Arabidopsis thaliana exhibit diverse expression patterns and potentially play roles in signaling pathways in other tissues.